The Combined Effect Of Physiotherapy Treatment And Lifestyle Modifications In Managing Cervicogenic Headache Among University Students - Deshpande, Neha; Poovishnu Devi, T. (Journal of Neonatal Surgery, 2025)
Background: Cervicogenic headache (CGH) is a prevalent issue among university students, generally associated with poor posture, excessive screen time, and musculoskeletal dysfunction. This research compares the effectiveness of physiotherapy alone vs physiotherapy coupled with lifestyle changes in improving CGH symptoms. Methods: There was a randomized clinical trial conducted at Krishna Vishwa Vidyapeeth in Karad, with 50 students (18-30 years old) diagnosed with CGH. Participants were randomly allocated to either Group A (physiotherapy only) or Group B (physiotherapy with lifestyle changes). Both groups received a four-week intervention that included spine mobilization, isometric neck exercises, and stretching. Group B additionally received instruction on proper posture, ergonomic changes, sleep hygiene, and stress management. Outcome assessments included headache frequency, pain severity, cervical range of motion (ROM), and the Headache Disability Index (HDI). Results: There was significant progress in both the groups after therapy. Pain intensity decreased by 46.59% for Group A and 60.83% for Group B (p < 0.05). Cervical ROM increased significantly, with 62.60% flexion and 58.76% extension (p < 0.0001). Lifestyle changes promoted symptom reduction, with regular headaches reducing by 46% in Group A and 62% in Group B. The HDI study revealed substantial improvements in everyday activities, emotional well-being, and social involvement. Conclusion: This research highlights how effectively an integrated approach works to treat cervicogenic headaches. Physiotherapy successfully lessens the symptoms of CGH, however including lifestyle changes provides better outcome. According to the results, an integrated intervention has better advantages and must be considered, particularly for those who